Kemajuan Budaya Masyarakat Makassar Abad XVII - Susmihara Susmihara (Jurnal Adabiyah: Humanities and Islamic Studies, 2016)
The plurality of social life of Makassar society in XVII century is a central point in the realization of gaining progress and performance in Makassar at the time. The plural life marked by principle of "high sea" and the tolerance among religious and the readiness Makassar government who politicized the society which has different background in mutual life.